Analysis of Indications of Caesarean Sections - Jasia Jabeen (Journal of Rawalpindi Medical College, 2013)
Background: To analyze indications and frequency of caesarean section. Methods:In this cross sectional study pregnant females , who underwent caesarean section during study period were enrolled. Indications for caesarean sections and caesarean section rates (CSR) were studied.. Results: During study period, total number of deliveries were 3049, out of which 1709 (56%) were caesarean sections. The commonest indication for caesarean section was repeat caesarean section (40.3%), followed by failed induction (13.5%) and fetal distress (11.2%) Conclusion: The rate of C-sections is high. Regular audits of CSR and indications for caesarean sections will help to reduce CSR.